2011
DOI: 10.1096/fj.10-178558
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal nicotinic receptors control novel social interaction between mice

Abstract: Social behavior is a defining mammalian feature that integrates emotional and motivational processes with external rewarding stimuli. It is thus an appropriate readout for complex behaviors, yet its neuronal and molecular bases remain poorly understood. In this study, we investigated the role of the mouse prefrontal area, particularly the involvement of β2-subunit nicotinic receptors (β2*-nAChRs) in a paradigm of social behavior with concurrent motivations. We previously observed that mice lacking β2*-nAChRs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
125
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 52 publications
9
125
2
Order By: Relevance
“…It has been reported that the β2 subunit is involved in the dendritic morphogenesis of pyramidal neurons, and in particular, in the circuits that contribute to the high-order functional connectivity of the cerebral cortex (40). These defects in the maturation of the cerebral cortex that have been reported in the β2 KO mice could contribute to the observed behavioral deficits (4,13,16). However, our data reveal that pharmacological intervention with nicotinic antagonists is enough for the disruption of USF mechanisms.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…It has been reported that the β2 subunit is involved in the dendritic morphogenesis of pyramidal neurons, and in particular, in the circuits that contribute to the high-order functional connectivity of the cerebral cortex (40). These defects in the maturation of the cerebral cortex that have been reported in the β2 KO mice could contribute to the observed behavioral deficits (4,13,16). However, our data reveal that pharmacological intervention with nicotinic antagonists is enough for the disruption of USF mechanisms.…”
Section: Discussionmentioning
confidence: 45%
“…For example, deletion of the α7 and β2 nAChR subunits in mice impairs behaviors, such as exploration and attention (12)(13)(14)(15)(16). Importantly, lesions of the prelimbic cortex (PrLC) in WT mice cause deficits in social behavior, similar to those observed in β2 knock-out (KO) mice, whereas re-expression of the β2 subunit in the PrLC of β2 KO mice rescues their social interaction (4). Similarly, re-expression of β2 subunits in the PrLC of β2 KO mice fully restored their attentional performance in the five-choice serial reaction time task (16).…”
mentioning
confidence: 99%
“…Re-expressing the 2 nAChR subunit in the prefrontal cortex also improves social abnormalities in this knockout mouse. Increased social interaction and decreased novel exploration in a social interaction paradigm with concurrent motivation was ameliorated after stereotaxically injecting the 2 nAChR subunit into the prelimbic area of the prefrontal cortex (PFC) (Avale et al, 2011). As previously mentioned, nAChR dysfunction is also implicated in several other neurological disorders with repetitive behavior.…”
Section: Nachrs Modulate Multiple Behaviors Deficient In Asdmentioning
confidence: 83%
“…Dichter et al, 2009;Ho et al, 2012), and in animal models (Avale et al, 2011;Covington et al, 2010Stack et al, 2010; but see Kumar et al, 2013). In the latter, prefrontal cortex damage, whether widespread (Gonzalez et al, 2000;Shah and Treit, 2003) or localized to the prelimbic cortex (Avale et al, 2011), has been reported to increase social exploration. In contrast, anterior cingulate lesions have yielded a reduction in social interest, rather unaffected by orbitofrontal lesions (Rudebeck et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, peripubertally stressed rats showed reduced motivation to explore a juvenile conspecific versus an object in the threechambered test (M arquez et al, 2013), a task used in non-human primates and rodents (Bauman et al, 2013;Moy et al, 2004) that can be considered akin to social approach-avoidance tasks used in humans (Heuer et al, 2007;Roelofs et al, 2009). Particularly susceptible to the long-term effects of this form of peripubertal stress is the prefrontal cortex (M arquez et al, 2013), the engagement of which has been shown to be critically involved in social behaviors in humans (Dichter et al, 2009;Ho et al, 2012) and in animal models (Avale et al, 2011;Covington et al, 2010;Stack et al, 2010).…”
mentioning
confidence: 99%